[Ground level construction plans for Kennedy Library] - P. K. Phillips::::::photographer::: (1970)
A color-coded diagram of the ground level construction plans for Kennedy Library. This depiction includes the atrium and other resources available on this level of the building, along with where the building is situated, in relation to the "existing building" (Building 34) and North Perimeter Road.